Tigger & Pooh and a musical too [videorecording (DVD)] - Hartman, David; Dubuc, Nicole, 1978-; Hohlfeld, Brian; Stefan, Dean (Disney DVD., 2009)
"Strike up the band with Pooh, Tigger, Darby and all your favorite friends in a spectacular full-length movie featuring seven original songs"--Container.